(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Two monuments in the early provincial gallo-roman environment are examined and compared with one another. Both deal with Celtic and Roman gods in the meanings of self-consciousness, identity and Romanization. The pillar of the nautae Parisiaci is here dated to the years 14 to 16 AD as a votive of the tribe of Parisi military and auxiliary units formed out of the tribe giving the members the double identity of being Celtic (Parisian) and Roman simultaneously. This is demonstrated by a balanced mixture of Gallic and Roman gods and goddesses. On the other side stands a votive altar from Noricum (upper Austria) from the middle of the 1st century AD, thus in an area long inhabited by the tribe of Boii and later dominated by the Noricans. Here a relief depicts a Celtic god with a wheel, most likely Taranis, but the inscription mentions Iuppiter only. So, what motifs or processes stand behind this different treatment of Celtic gods within a couple of decades?